Determinants and implications of the growing scale of livestock farms in four fast-growing developing countries - Delgado, Christopher L.; Narrod, Clare; Tiongco, Marites; Barros, Geraldo Sant'Ana de Camargo; Catelo, Maria Angeles O.; Costales, Achilles; Mehta, Rajesh; Naranong, Viroj; Poapongsakorn, Nipon; Sharma, Vijay Paul; de Zen, Sergio (International Food Policy Research Institute, 2008)
Overall, the study concludes that in many cases smallholders other than the smallest backyard producers will be able to stay in the livestock business for a long time. If the opportunity cost of family labor rises and begins to approach local market wage rates, however, then much of the competitiveness of smallholder operations compared with large farms is vitiated. Furthermore, emerging disease threats and environmental backlash suggest that large and small producers will sink or rise together based on their ability to act collectively to deal with emerging threats. Finding ways to increase synergies between the two groups is very much in the social interest. Finally, if supply chains become longer, wider, and more anonymous, the future for independent livestock farming, whether large or small, will eventually depend on the options for integration with input supply and output marketing operations.